2001
DOI: 10.1002/jmv.2034
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of antiviral MxA protein in peripheral blood of patients with A chronic disease of unknown etiology*

Abstract: Interferon alpha (IFN-alpha) is synthesized in response to viral infections. MxA protein, induced specifically by IFN-alpha and beta, expressed in peripheral blood cells, is detected more consistently than circulating IFN-alpha in serum of patients with viral infections. Thus, activation of the IFN-alpha/MxA system can be used as additional marker of the presence of a virus in patients. Therefore MxA protein and IFN-alpha levels were measured in patients with multiple sclerosis (MS), a chronic neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This finding is not new and is most likely due to heterogeneity in the immunology of patients with MS. Indeed, Chieux and co-authors [37] reported that, in contrast to moderate differences in MxA expression in healthy individuals, clinically ability, including the immunological (e.g. change in Th1/Th2 ratio or cross-talk from other cytokineactivated pathways) and genetic characteristics of patients [38][39][40][41].…”
Section: Discussionmentioning
confidence: 96%
“…This finding is not new and is most likely due to heterogeneity in the immunology of patients with MS. Indeed, Chieux and co-authors [37] reported that, in contrast to moderate differences in MxA expression in healthy individuals, clinically ability, including the immunological (e.g. change in Th1/Th2 ratio or cross-talk from other cytokineactivated pathways) and genetic characteristics of patients [38][39][40][41].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, our findings lead to the hypothesis that MS patients with − 88T haplotype express much higher levels of MxA protein in response to IFNs, and those who have − 123A express MxA in high levels without IFNs. Chieux et al [9] have demonstrated increased levels of MxA protein in MS without IFN injection. They speculated that the higher levels of MxA resulted from activation of the whole IFN-MxA system via viral infection.…”
Section: Discussionmentioning
confidence: 98%
“…28 The increased expression of MxA confirms data from a previous report that also showed increased expression of MxA at the protein level in PB cells of RRMS patients. 29 Accordingly, Chieux et al 29 also showed increased levels of IFN-a in the serum of MS patients.…”
Section: Discussionmentioning
confidence: 99%